International Legal Rules of the Temporary Entry (Admission) of Goods into the Territory of States - Natalia A. Vorontsova (Московский журнал международного права)
The multifaceted economic cooperation of States among themselves is not possible without the establishment of international rules of such cooperation in various areas. In order to promote the development of foreign trade, the States elaborate national legislation in such a manner that all procedures to be simple, easy for understanding, predictable and corresponding to generally accepted international standards. The article reviews international legal rules of movement of goods from one state to another on a transitory basis with the provision of exemption.